The use of an analytic model for implementing an innovative method for teaching day-lighting in Architecture - Atanasio, Veridiana (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Daylighting considerations influence the whole design process and should incorporate conceptual and aesthetics topics as well as technical ones. In spite of advances in both research and technological devices in the last decades, there are several barriers that make it difficult the effective application of such advances in architectural design. Recent studies have pointed out the lack of adequate understanding of the day-lighting phenomenon as one of the major barriers. This article presents the development of a Virtual Learning Environment (VLE), an innovative teaching method for improving students’ understanding about the lighting phenomenon, approaching the light path and its modifications generated by the main architectural design variables.